BUSINESS OPPORTUNITIES FOR NOVICE BUSINESS PEOPLE IN MOMENT CAR FREE DAY KUNINGAN REGENCY WEST JAVA - Wachyuni Wachyuni; Wely Hadi Gunawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
ABSTRACT This research is set against the backdrop of the rise of car free day events utilized not only to reduce air pollution, but also as a meeting place between groups of people in sports activities, cultural arts, and economics. As a public space, many businesses are used as a medium to promote the products they create. In this event also brings up budding business people. This research is intended to find out the business opportunities made by novice businesses by using SWOT analysis strategy of IFAS and EFAS matric models. This research was conducted with a quantitative and qualitative approach. This sampling method is probability sampling, with proportional random sampling technique. The data analysis tool used is swot analysis. As a result, budding businesses are taking advantage of opportunities by building permanent businesses instead of just on Car Free Day, innovating, and building networks and using digital marketing to introduce products and also to increase product sales, create products and services that differ from competitors, manage finance and planning and analysis properly and maintain the quality of products they offer to the public. Keywords : Business Opportunities, Strength, Weaknesses, Opportunities, Threats, IFAS, EFAS